Insight into the influence of biochar on nitrification based on multi-level and multi-aspect analyses of ammonia-oxidizing microorganisms during cattle manure composting. (November 2021) - Deng, Liting; Zhao, Mingming; Bi, Ruixin; Bello, Ayodeji; Uzoamaka Egbeagu, Ugochi; Zhang, Jizhou; Li, Shanshan; Chen, Yanhui; Han, Yue; Sun, Yu; Xu, Xiuhong
Graphical abstract: Highlights: Biochar inhibited the AOA amoA gene transcription but enhanced that of AOB. Crenarchaeota and Nitrosospira were the key taxa mediating nitrification. Biochar altered the key AOMs taxa mediating NRV and the interactivity between taxa. AOA and AOB could concurrently participate in nitrification and denitrification. M−LAA of AOMs could better explain the influence of biochar on nitrification. Abstract: In this study, influence of biochar on nitrification was explored using multi-level (DNA, RNA, protein) and multi-aspect (diversity, structure, key community, co-occurrence pattern and functional modules) analyses (M−LAA) of ammonia-oxidizing microorganisms (AOMs) during cattle manure composting. Biochar addition increased the copy numbers and diversity of AOMs, restricted (36.02%) the amoA gene transcripts of archaea but increased (24.53%) those of bacteria, and reduced (75.86%) ammonooxygenase (AMO) activity. Crenarchaeota and Thaumarcheota mediated NH4 + -N, Unclassified_k_norank_d_Archaea and Crenarchaeota regulated AMO activity and potential ammonia oxidation (PAO) rates. Nitrosomonas and Nitrosospira were the predominant microbial taxa influencing NH4 + -N variation and PAO rates, respectively. Additionally, both Crenarchaeota and Nitrosospira played crucial roles in mediating NO3 – -N and NO2 – -N. Furthermore, biochar altered the network patterns of AOMs community by changing the keystone species and the interactivity among communities. These findings indicated that influence of biochar on nitrification could be better explained using M−LAA of AOMs.